ADAPTATION OF RADIO BROADCASTING MEDIA TO LEAD TO A NEW MEDIA IN THE ERA OF MEDIA INTEGRATION: A CASE STUDY OF A COMMUNITY RADIO STATION IN NAKHON PATHOM PROVINCE - Wannasiri , Phanom; Khotbua, Chanakasem (Journal of MCU Nakhondhat, 2023)
This research article aims to study 1) factors affecting radio broadcasting media adaptation, 2) forms of content adaptation of radio broadcasting media, and 3) forms of radio broadcasting media adaptation. in the management of media organizations which leads to a new media in the era of media convergence A Case Study of a Community Radio Station in Nakhon Pathom Province is a quantitative research The sample group was personnel working at a community radio station in Nakhon Pathom Province. with the right to operate a business, amounting to 8 stations, selected by purposive sampling From personnel in different positions with equal proportions, 10 people per station, a total of 80 people Research tools as a questionnaire The statistics used in the research were the mean value, the deviation of the gauge. correlation coefficient using Spearman coefficient statistics Interpret the meaning according to the criterion for dividing the mean score. The results of the study revealed that 1) The factors that highly affect the adaptation of radio broadcasting media are management policies, budgets, organizations, changes in listening behavior of listeners, and laws; The content of the radio broadcasting media is the addition of new channels, commenting, and talking through online channels. Publishing via social media (Social Media) such as Facebook, Youtube, Tiktok or opening a podcast with new content, video content through live broadcasts (live) and 3) the form of adaptation of radio broadcasting media. The management of the community radio station's media organization in Nakhon Pathom Province is to reduce the number of personnel. to reduce production costs Reducing the team and developing the potential of personnel to be able to work in a variety of ways. organizational restructuring marketing strategy building Adjustment of additional investment in technology.